Na ile informator jest wiarygodnym źródłem danych dialektologicznych? = To what extent is an informant a reliable source of dialectological information? - Kobus, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents research methodology used in the Centre for Dialectology at Adam Mickiewicz University in Poznań, particularly the criteria according to which informants are selected for dialectal research in the region of Greater Poland (Pol. ?Wielkopolska?).
Keywords: informator; bariery komunikacyjne; język mieszkańców wsi; informant; communication barriers; language of country dwellers